1987
DOI: 10.1111/j.1530-0277.1987.tb01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dysfunction and Aging among Male Alcoholics and Social Drinkers

Abstract: The relationship between aging and various drinking styles was examined. Four age groups (25-34, 35-44, 45-54, and 55-65 years) and four drinking styles (nondrinkers, social drinkers, alcoholics, and abstinent alcoholics) were compared. A battery of eight neuropsychological tests was administered to 322 men; 72 nondrinkers, 100 social drinkers, 58 abstinent alcoholics, and 92 alcoholics. Cognitive dysfunction related to aging was found to be a more significant factor than decline with alcohol use. Cognitive dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Several recent studies of elderly social drinkers have found no association or only weak associations between cognitive performance and alcohol consumption measured either concurrently or retrospectively 20 21 22 23 24 25. Furthermore, any correlations found have tended to disappear when other factors were controlled statistically.…”
Section: Discussionmentioning
confidence: 92%
“…Several recent studies of elderly social drinkers have found no association or only weak associations between cognitive performance and alcohol consumption measured either concurrently or retrospectively 20 21 22 23 24 25. Furthermore, any correlations found have tended to disappear when other factors were controlled statistically.…”
Section: Discussionmentioning
confidence: 92%
“…Positive effects for women, but not for men, have been reported (Dufouil et al, 1997), and a failure to find any differences in cognitive performance between current and abstinent individuals has also been reported (Dent et al, 1997). Studies in middle-aged (ages 30-60) samples are also inconclusive, with smaller clinical studies (Emmerson et al, 1988;Page & Cleveland, 1987;Waugh et al, 1989;Williams & Skinner, 1990) and large community-based studies (Cerhan et al, 1998;Parker et al, 1991) showing both beneficial and detrimental effects.…”
Section: Introductionmentioning
confidence: 87%
“…A comprehensive analysis of the impact of drinking and smoking on cognition should also include analyses not only by category of use (abstainer, user, ex-user), but also of lifetime consumption. In one report (Page & Cleveland, 1987), for example, significant results were obtained for comparisons of groups based on category of smoking use, but not for analyses based on pack-year history. Finally, adequate measurement of cognitive function should include more sensitive measures of global function, as well as measures of important domains of cognition.…”
Section: Introductionmentioning
confidence: 90%
“…Today, significant numbers of elderly alcoholics are appearing for treatment, more in fact than any previous time (Page and Cleveland, 1987). Whether this is due to greater actual needs for treatment or merely a better identification of geriatric alcoholics is unclear.…”
Section: Clinical Commentsmentioning
confidence: 99%